Sustaining Islamic Educational Traditions: A Structural-Functional Analysis of Arab Pegon Translation in Pesantren Fathul Ulum - MZ, Isniyatun Niswah; Ahid, Nur; Rahman, Zayad Abd (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2025)
The kitab kuning (classical Islamic texts) has long been regarded as an authoritative reference in the pesantren (Islamic boarding school) tradition. These books, written by classical Islamic scholars, have been studied across generations and are viewed as time-tested sources of Islamic knowledge grounded in the Qur’an and Hadith. One distinctive method used in pesantren to comprehend the kitab kuning is the maknani method—a translation approach utilizing Arab Pegon, a modified Arabic script adapted to the Javanese language. The use of Arab Pegon serves not only as a learning aid but also holds historical significance in the spread of Islam in the Indonesian archipelago. Pesantren Fathul Ulum in Kwagean, Kediri, is one of the Islamic boarding schools that continues to preserve this Pegon translation tradition in the study of kitab kuning. This qualitative research aims to examine the tradition of translating kitab kuning into Arab Pegon at Pesantren Fathul Ulum through the lens of Talcott Parsons’ structural-functional theory, particularly the AGIL framework (Adaptation, Goal Attainment, Integration, and Latency). The findings reveal that Pegon translation functions both as a pedagogical tool and a socio-cultural mechanism that sustains the pesantren system. The pesantren’s ability to adapt its teaching methods to the diverse backgrounds of its students reflects the function of adaptation. The design of a learning system that preserves classical Islamic knowledge demonstrates the function of goal attainment. The function of integration is evident in the social structure and collective use of linguistic codes, thereby strengthening community cohesion within the pesantren. Meanwhile, the function of pattern maintenance is realized through the preservation of values, norms, and educational traditions across generations. Thus, the practice of Arab Pegon translation plays a vital role in maintaining the existence of pesantren as a traditional Islamic educational institution amid the dynamics of social change.